Implementation of the Space Strategy and National Space Legislation in Poland - Elzbieta MRENCA (Communications of International Proceedings, 2021)
The space sector, which is increasingly important for the global economy, is a driver of innovation and scientific, technical, as well as technological progress.  The Polish Space Strategy outlines the directions of development for the space sector in Poland. It includes the creation of framework conditions and support instruments to foster the development of that sector. Also, the aim of the strategy is to increase the innovativeness and competitiveness of related areas, as well as to improve the overall security level. This article focuses on legal aspects of implementation of one of the objectives of the Polish Space Strategy, namely the creation of favorable conditions for the development of the space sector in Poland. Developing a bill on the National Register of Space Objects is one of the ways to achieve this objective. Therefore, the aim of the current study is to analyze the legislative process in Poland in the field of national space law.  This bill is intended to include, among other things, regulations for maintaining a registry of space objects launched by Polish entities. Moreover, this information would be, in each in case, forwarded to the Secretary-General of the United Nations.
Keywords: Space Sector; Polish Space Strategy; Space Law; The Legislative Process